Immediacy of evidence examination in the system of general conditions of criminal trials - Bibilo, Valentina N. (Journal of the Belarusian State University. Law, 2026)
This article examines the system and significance of general conditions for criminal trial proceedings. These include provisions concerning the principles of criminal procedure, participants in the court hearing, the rendering of judicial decisions, etc. General conditions for trial proceedings are a legislative technique that helps to clearly understand the content of each stage of the trial. Among these, the immediacy of the evidence examination is of the greatest importance, as the court must base its decisions only on evidence directly perceived by the court. Immediacy is a method of examining evidence in criminal proceedings.
Keywords: court; trial; principles; immediacy of evidence examination; method; criminal trial; criminal case